Government Policy In Issuing Letter Of Recognition Of Land Rights: (Study in North Musi Rawas Regency) - Hartawan (IHSA Institute, 2022)
The problem of this research was regarding the alienation certificate (SPH) like: 1). less awareness of people about the importance of alienation certificate, 2). the lack of socialization from the related institute about the importance of this alienation in village or district, 3). lack of education on people about the importance of this land affairs document, which in the document regulation was arranged regarding the realization of the land affairs. This research aimed to know the policy of alienation certificate (a study in Rawas Ilir district North Musi Rawas). This study used qualitative method and the data analysis technique were data reduction, data display, and conclusion drawing or verification. The results of this study indicated that some indicators as follow: Communication and bureaucracy had been achieved the indicators represents the implementation of SPH in the village. Therefore it can be concluded that policy of alienation certificate policy in Rawas Ilir district has been achieved.